The development of Leishmania turanica in sand flies and competition with L. major - Chajbullinova, Alsu; Votypka, Jan; Sadlova, Jovana; Kvapilova, Katerina; Seblova, Veronika; Kreisinger, Jakub; Jirku, Milan; Sanjoba, Chizu; Gantuya, Sambuu; Matsumoto, Yoshitsugu; Volf, Petr (Parasites & vectors, 2012)
BACKGROUND: In Central Asian foci of zoonotic cutaneous leishmaniases, mixed infections of Leishmania turanica and L. major have been found in a reservoir host (the great gerbil, Rhombomys opimus) as well as in the sand fly vector Phlebotomus papatasi, but hybrids between these two Leishmania species have never been reported. In addition, the role of sand fly species other than P. papatasi in L. turanica circulation is not clear. METHODS: In this work we compared the development of L. turanica in three sand fly species belonging to different subgenera. In addition, we studied experimental co-infections of sand flies by both Leishmania species using GFP transfected L. turanica (MRHO/MN/08/BZ18(GFP+)) and RFP transfected L. major (WHOM/IR/-/173-DsRED(RFP+)). The possibility of Leishmania genetic exchange during the vectorial part of the life cycle was studied using flow cytometry combined with immunofluorescent microscopy. RESULTS: Late-stage infections of L. turanica with frequent colonization of the stomodeal valve were observed in the specific vector P. (Phlebotomus) papatasi and in the permissive vector P. (Adlerius) arabicus. On the other hand, in P. sergenti (the specific vector of L. tropica), L. turanica promatigotes were present only until the defecation of bloodmeal remnants. In their natural vector P. papatasi, L. turanica and L. major developed similarly, and the spatiotemporal dynamics of localization in the sand fly gut was the same for both leishmania species. Fluorescence microscopy in combination with FACS analyses did not detect any L. major / L. turanica hybrids in the experimental co-infection of P. papatasi and P. duboscqi. CONCLUSION: Our data provide new insight into the development of different leishmania parasite species during a mixed infection in the sand fly gut. Despite the fact that both Leishmania species developed well in P. papatasi and P. duboscqi and did not outcompete each other, no genetic exchange was found. However, the ability of L. turanica to establish late-stage infections in these specific vectors of L. major suggests that the lipophosphoglycan of this species must be identical or similar to that of L. major.
Keywords: zvířata; Animals; zelené fluorescenční proteiny; luminescentní proteiny; mikrobiální interakce; Phlebotomus; Green Fluorescent Proteins; Leishmania; barvení a značení; gastrointestinální trakt; Microbial Interactions; Staining and Labeling; Luminescent Proteins; fluorescenční mikroskopie; Microscopy, Fluorescence; Gastrointestinal Tract